Improved performance in aluminium oxide tool inserts via post sintering using hybrid microwave energy - Mohamed Ariff, Tasnim Firdaus; Firdaus, Muhammad; Norhafiz, Mohd; Iqbal, Mohammad; Hilmy, Irfan (PAK Publishing, 2014)
This research investigates the effect of hybrid microwave energy toward the enhancement of tool life in Al₂O₃ inserts. Post sintering was done using conventional and hybrid microwave sintering at 600°C for 15 mins and compared the findings with the original available commercial inserts. Mechanical testing such as density, hardness and compression strength were performed together with the micro structural analysis using Scanning Electron Microscope (SEM) was done. Tool life of these Al₂O₃ inserts were analysed through dry machining using three different cutting speeds ( 245, 305 and 381 m/min) at the feed rate of 0.2 mm/rev and depth of cut of 0.2 mm. Two different workpieces were used in this research; T6061 Aluminium Alloy and Hardened Steel. Results have shown that the density and hardness remain quite similar with or without the post sintering effect. However, the material became slightly more brittle upon post sintering where conventional sintering produced a compression strength of 0.07 MPa while the hybrid microwave sintering produced a compression strength of 0.21 MPa. Tool life of Al₂O₃ inserts in dry machining of T6061 Aluminium alloy and Hardened Steel has increased by 27.0-40.0 % and 30.6-39.1 % respectively for the hybrid microwave post sintering.